The Effect of Profitability and Company Size on Company Value with Good Corporate Governance as A Moderating Variable Listed on The Indonesia Stock Exchange - Selviana Lauren; Riswan (PT. Altaf Publishing Corp, 2026)
This study aims to analyze the effect of profitability and firm size on firm value, with Good Corporate Governance (GCG) as a moderating variable, in banking sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The study employed a quantitative approach using purposive sampling, resulting in 23 companies with a total of 69 observations. The data used were secondary data derived from annual financial reports published by the IDX. The analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS. The results of the t-test indicate that profitability has a positive and significant effect on firm value, and firm size also has a positive and significant effect on firm value (p = 0.000). The coefficient of determination shows an Adjusted R² value of 0.65, indicating that 65% of the variation in firm value can be explained by profitability, firm size, and GCG variables, while the remaining [35%] is influenced by other factors outside the model. Furthermore, the MRA results demonstrate that Good Corporate Governance, proxied by independent commissioners and the audit committee, significantly moderates the relationship between profitability and firm value, as well as the relationship between firm size and firm value. These findings suggest that strong financial performance and larger company scale contribute to higher firm value, and the implementation of effective GCG mechanisms strengthens this relationship by enhancing investor confidence. This research is expected to serve as a reference for company management and investors in making strategic decisions related to financial performance and corporate governance practices.